Patient Education 101. - Ulrich, Beth; Wright, Linda (Nephrology Nursing Journal)
Patient education is a professional responsibility of all registered nurses (RNs); however, many RNs have never been taught how to teach, and specifically, how to teach patients. Teaching is a specialty all its own, and requires knowledge of principles and practices of teaching. This article provides basic information for RNs who are providing patient education, including learning theories and styles, learning environments, teaching strategies (communication, teach-back, microlearning, feedback, debriefing and reflective practice, educational materials), patient assessment (motivational interviewing, health literacy), planning (goals and objectives), competency, implementation, and evaluation.